PHARMACOGNOSTICAL, PRELIMINARY PHYTOCHEMICAL SCREENING AND IN VITRO ANTIOXIDANT ACTIVITY OF HYDROMETHANOL EXTRACT OF GORDONIA DIPTEROSPERMA KURZ. - LAPASAM, PHAIBIANG; LALTHASANGA, ANDREW; NONGKHLAW, FREDDY TEILANG; PUIA, ZOTHAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This research is to evaluate the pharmacognostic parameter, phytochemical analysis, and in vitro antioxidant properties of hydromethanol extract. Method: This study carries out the collection and authentication of the plant, extraction, pharmacognostic study, preliminary phytochemical screening, and antioxidant property of leaves hydromethanol extract were evaluated by scavenging the following free radicals – DPPH (2,2-diphenyl- 1-picrylhydrazyl), hydrogen peroxide, nitric oxide, and reducing power. One-way analysis of variance (ANOVA) followed by Dunnett’s test was performed. The minimum value of *p˂0.05 considered as significant, **p˂0.01 and ***p˂0.001. Results: Powder microscopy of the leaves showed the presence of stomata, calcium oxalate crystals, trichome, fibers, and oil glands. The total ash was considered to be 3.75%, water-soluble ash 1.25%, and acid-soluble ash 3%. Hydromethanol (3:7) extract yielded 38.8%, moisture content 15.6%. Preliminary phytochemical screening of the extract showed the presence of carbohydrates, glycoside, saponin, phenol, tannin, flavonoid, and steroid. The total flavonoid content was considered to be 32.25 mg/g of quercetin and the total phenolic content of the extract was found 610 mg/g of gallic acid. The IC50 radical scavenging effect of extract and gallic acid was considered to be 3.62 and 3.46 for 2,2-diphenyl-1-picrylhydrazyl, 10.4 and 24.73 for hydrogen peroxide, and 48.76 and 58.83 for nitric oxide. Conclusion: The phytochemical constituents of the extract were well-known pharmacologically active chemicals and significant antioxidant potential was shown by the extract. This study finds out the rationality of the use of this plant as a medicinal plant. Further studies would be needed to explore their potential as a treatment for fever, diarrhea, and dysentery.